Variability and interpopulation differentiation of the rare species Gueldenstaedtia monophylla Fisch. (Fabaceae) - I. Yu. Selyutina; E. S. Konichenko; O. V. Dorogina (Вавиловский журнал генетики и селекции)
Genetic variability of the rare species Gueldenstaedtia monophylla from 7 natural populations in the central part of its range (Ongudai district, Altai Republic) was studied. To characterize the genetic diversity of this rare relict species at the population level, SDS-electrophoresis of seed storage proteins was used. Polypeptide spectra of seeds contained from 17 to 32 protein components, of which 28 were polymorphic. The populations of G. monophylla were revealed to have a sufficiently high level of genetic polymorphism, the genetic similarity index within the populations studied ranged from 0.673 to 0.813. The highest variability of seed storage proteins was found in the populations Inegen (0.673) and Malaya Inya (0.734). The lowest level of variability of the polypeptide spectra was in the population Bol’shoy Yaloman (0.813). The Nei genetic distance between the populations studied was 0.018–0.215, the greatest distance in the protein spectra was found between Inegen and Malaya Inya (0.215). Inegen was the most remote from the other populations, the Nei distance between this population and all other populations varying from 0.113 to 0.215. With AMOVA, it was found that the share of intra-population variability is 53 % and inter-population, 47 %. Perhaps this high genetic diversity in populations of G. monophylla is provided and maintained by such biological characteristics of the species as cross-pollination, high life expectancy and a long reproductive period. The results of our study suggest that some rare species are able to maintain high levels of genetic diversity, even in a small-size population. The relatively high level of genetic variability indicates that the current genetic drift and inbreeding do not pose a threat to the survival of the species.